27.6k views
1 vote
F(x) = 3x2 – 4x – 1
g(x) = –2x + 5
Find: (gof)(x)

1 Answer

1 vote

Answer:


(g\circ f)(x)=-6x^2 +8x +7

Explanation:

The Composite Function

Given f(x) and g(x) real functions, the composite function, named (g\circ f)(x) is defined as:


(g\circ f)(x)=g(f(x))

For practical purposes, it's found by substituting f into g.

Given the functions:


f(x) = 3x^2 - 4x - 1


g(x) = -2x + 5

We need to find


(g\circ f)(x)=g(f(x))

Replace f into g:


(g\circ f)(x)=-2(3x^2 - 4x - 1) + 5

Operating:


(g\circ f)(x)=-6x^2 +8x +2 + 5

Reducing:


(g\circ f)(x)=-6x^2 +8x +7

Thus,


\boxed{(g\circ f)(x)=-6x^2 +8x +7}

User TypedSource
by
6.1k points